MANAJEMEN KOMUNIKASI MEDIA DIGITAL DI PERGURUAN TINGGI SWASTA WILAYAH NON-PERKOTAAN (STUDI KASUS PTS DI SULAWESI BARAT) - Darmawati Kadir; Muhammad Ridwan Arif; Muhammad Asdar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2023)
The research aims to analyze the management of digital communication media used in private university organizations (PTS) with a case study of PTS in West Sulawesi, and evaluate the types of digital communication media used. This research was conducted on a sample of three campuses in West Sulawesi Province. This research is qualitative with a case study approach, with the paradigm used is the constructivism paradigm. The sample was analyzed using question construction data based on the research variables raised, so that the perceptions of the organizational team consisting of structural officials, lecturers, and students were collected. The results of this study reveal that the application of communication media in the digital era is closely related to management patterns that include planning, implementation, control, and evaluation stages with a multi-channel communication approach. Digital media such as instant messaging applications, webinar platforms, and social media play an important role in supporting interaction and collaboration between students, lecturers, and university leaders in various academic and administrative aspects. The use of these various communication channels successfully supports information distribution, coordination, exchange of views, and expression of feelings to achieve organizational goals. Although guidelines and policies still need to be improved, the positive impact of digital media in education, research, and community service, especially during the pandemic, is clear, and can even resolve internal conflicts.